Vickrey auction vs BDM: Difference in bidding behaviour and the impact of other-regarding motives - Niall Flynn; Christopher Kah; Rudolf Kerschbamer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
In an experiment we first elicit the distributional preferences of subjects and then let them bid for a lottery, either in a Becker-DeGroot-Marschak (BDM) mechanism or a Vickrey auction (VA). Standard theory predicts that altruistic subjects underbid in the VA - compared to the BDM - while spiteful subjects overbid in the VA. The data do not confirm those predictions. While we observe aggregate underbidding in the VA, the result is not driven by the choices of altruistic subjects.
Keywords: C91; C72; 330; Distributional preferences; BDM; Vickrey auction